Central Banking at a Crossroads: Europe and Beyond - Charles A. E. Goodhart; Daniela Gabor; Jakob Vestergaard; Ismail Ertürk (Anthem Press, 2014)
This book reflects on the innovations that central banks have introduced since the 2008 collapse of Lehman Brothers to improve their modes of intervention, regulation and resolution of financial markets and financial institutions. Authors from both academia and policy circles explore these innovations through four approaches: "Bank Capital Regulation" examines the Basel III agreement; "Bank Resolution" focuses on effective regimes for regulating and resolving ailing banks; "Central Banking with Collateral-Based Finance" develops thought on the challenges that market-based finance pose for the conduct of central banking; and "Where Next for Central Banking" examines the trajectory of central banking and its new, central role in sustaining capitalism.
Keywords: 330; Internationaler Finanzmarkt; Finanzmarktregulierung; Zentralbank; Geldpolitik; Welt